THE FOURTH ESTATE: VIOLENCE, PARALLEL NORMATIVITY, AND SOCIAL CONTROL EXERCISED BY DRUG TRAFFICKING - Lopes de Assis, Leonard (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes drug trafficking as a punitive factual power exercised parallel to the State in territories marked by institutional fragility or absence. It argues that criminal organizations construct a parallel normative order capable of regulating social conduct, resolving conflicts, and imposing extrajudicial sanctions, including the physical elimination of perpetrators of crimes against women and children. The article demonstrates that such practices do not constitute alternative justice, but rather an extreme form of armed social control, grounded in selective violence and the economic rationality of the illicit drug market. This model of governance is structurally incompatible with the Democratic Rule of Law and with Human Rights, as it replaces legal guarantees with coercion, fear, and the administration of death.